2009
DOI: 10.1186/1471-2180-9-212
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Mycobacterium avium subspecies paratuberculosis across host species and European countries with evidence for transmission between wildlife and domestic ruminants

Abstract: BackgroundMycobacterium avium subspecies paratuberculosis (Map) causes an infectious chronic enteritis (paratuberculosis or Johne's disease) principally of ruminants. The epidemiology of Map is poorly understood, particularly with respect to the role of wildlife reservoirs and the controversial issue of zoonotic potential (Crohn's disease). Genotypic discrimination of Map isolates is pivotal to descriptive epidemiology and resolving these issues. This study was undertaken to determine the genetic diversity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
114
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 52 publications
6
114
0
7
Order By: Relevance
“…Most of these studies were based on existing isolate collections, and showed a fair amount of homogeneity within M. paratuberculosis strains and revealed that M. paratuberculosis strains from human infections were less diverse compared to cattle (Wynne et al, 2011). Results were derived from several methods making it difficult to make direct comparisons, including IS1311 restriction fragment length polymorphism (RFLP) analyses (Whittington et al, 2000;Motiwala et al, 2003;Singh et al, 2010b;Okuni et al, 2012;Liapi et al, 2015), (Stevenson et al, 2009;Fernandez-Silva et al, 2012) randomly amplified polymorphic DNA (RAPD) (Pillai et al, 2001), multi-locus short sequence repeat sequencing (MLSSR) (Fernandez-Silva et al, 2012), Multiplex PCR of IS900 integration loci (MPIL) (Motiwala et al, 2004), short sequence repeats (SSR) (Ghadiali et al, 2004), and single nucleotide polymorphisms (SNPs) (Wynne et al, 2011). A tally of the type of M. paratuberculosis (e.g.…”
Section: Molecular Epidemiology Of M Paratuberculosismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies were based on existing isolate collections, and showed a fair amount of homogeneity within M. paratuberculosis strains and revealed that M. paratuberculosis strains from human infections were less diverse compared to cattle (Wynne et al, 2011). Results were derived from several methods making it difficult to make direct comparisons, including IS1311 restriction fragment length polymorphism (RFLP) analyses (Whittington et al, 2000;Motiwala et al, 2003;Singh et al, 2010b;Okuni et al, 2012;Liapi et al, 2015), (Stevenson et al, 2009;Fernandez-Silva et al, 2012) randomly amplified polymorphic DNA (RAPD) (Pillai et al, 2001), multi-locus short sequence repeat sequencing (MLSSR) (Fernandez-Silva et al, 2012), Multiplex PCR of IS900 integration loci (MPIL) (Motiwala et al, 2004), short sequence repeats (SSR) (Ghadiali et al, 2004), and single nucleotide polymorphisms (SNPs) (Wynne et al, 2011). A tally of the type of M. paratuberculosis (e.g.…”
Section: Molecular Epidemiology Of M Paratuberculosismentioning
confidence: 99%
“…cattle, sheep, bison) found by species category is shown in Figure 4. Multiple fingerprinting techniques were used to show the diversity of M. paratuberculosis within populations, and it was argued that it is possible to demonstrate strain sharing within and across species by the degree of homogeneity between isolates (Stevenson et al, 2009 (Singh et al, 2010b;Sohal et al, 2014;Ahlstrom et al, 2015;Podder et al, 2015).…”
Section: Molecular Epidemiology Of M Paratuberculosismentioning
confidence: 99%
“…Genetic diversity among M. avium subspecies paratuberculosis strains has been investigated using molecular techniques, such as restriction fragment length polymorphism (RFLP) and IS900 analysis (IS900 RFLP) (3), pulsed-field gel electrophoresis (PFGE) (4), amplified fragment length polymorphism (AFLP) analysis (5), random amplified polymorphic DNA (RAPD) analysis (6), mycobacterial interspersed repetitive unit-variable number tandem repeat (MIRU-VNTR) analysis (7), and short-sequence repeat (SSR) analysis (8). However, these techniques have limited discriminatory power when applied to M. avium subspecies paratuberculosis; although this power can be increased by combining complementary genotyping techniques, it is often insufficient for accurately determining relationships among isolates or global epidemiological studies (9,10).…”
mentioning
confidence: 99%
“…Although the classification of strains into C, S, or B types may reflect a host preference, multiple strains of M. avium subsp. paratuberculosis can cross the species barriers and be isolated from a broad range of animal species (28,29,41). While the diverse M. avium subsp.…”
mentioning
confidence: 99%